Aplikasi Pengelolahan Data Surat Menyurat Menggunakan Framework Laravel 8 Berbasis Web - Ramadani, Ahmad; Hanafi, Muhammad (Journal of Computer Science and Informatics Engineering, 2022)
This web-based correspondence data processing application is an indispensable application in the process of collecting incoming mail. With this web-based correspondence data processing application, it is easier for agencies to collect data and store incoming file data. Data collection was carried out using observations and questions and answers to workers on the spot, observations were made on an object (letter) which was observed in the data collection process on the expedition and the process of the journey of the letter to each field. To overcome this, the use of information and communication technology in the form of computer media is also the reason why computer archives must be managed electronically. become easier, and more accurate.